(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2014)
This article is an overview of the experience of creative inspiration and the philosophical issues present. Potential applications for existential coaching are proposed with a view to allowing greater engagement with this key aspect of creative life which is often overlooked in modern life